Cast copies of a Neapolitan silver didrachm from the Berlin coin cabinet - Voukelatos, John (KOINON: The International Journal of Classical Numismatic Studies, 2020)
In 1900 the Berlin coin cabinet acquired a Neapolitan silver didrachm from the Imhoof-Blumer collection. The obverse depicts a head of Athena facing right and wearing a helmet decorated with a laurel branch. The reverse depicts an androcephalous bull walking to the right. The ethnic, in boustrophedon, runs from above the bull’s head, along his back, and then down behind him; it reads ΝΕΟΠΟΛΙ – Τ – ΗΣ.